Dual effects of muscarinic M(2) acetylcholine receptors on the synthesis of cyclic AMP in CHO cells: dependence on time, receptor density and receptor agonists - Michal, P; Lysíková, M; Tucek, S (British journal of pharmacology, 2001)
1. Muscarinic M(2) receptors normally inhibit the production of cyclic AMP via G(i) proteins, but a stimulatory component occurs in their effect at high agonist concentrations, believed to be based on the activation of G(s) proteins. We investigated the conditions which determine the occurrence and extent of the stimulatory component in CHO cells stably expressing muscarinic M(2) receptors. 2. Biphasic concentration-response curves (decline followed by return towards control values) were obtained after 10 min incubation with carbachol, oxotremorine-M, acetylcholine, arecoline and arecaidine propargyl ester, but the upward phase was missing with oxotremorine, methylfurmethide, furmethide and pentylthio-TZTP. Shortening the incubation favoured the occurrence of the stimulatory component. Carbachol (1 mM) and oxotremorine-M (1 mM) brought about net stimulation (above 100% of control) of cyclic AMP synthesis during 2 min incubations. The stimulatory components disappeared after the density of receptors had been lowered with oxyphenonium mustard. 3. All agonists stimulated the synthesis of cyclic AMP in cells pretreated with pertussis toxin. 4. Most differences between agonists regarding the stimulatory component of their effect on cyclic AMP synthesis could be explained by differences in their efficacy and the induced receptor internalization. 5. We propose that the G(s)-mediated stimulatory component of the effect of muscarinic M(2) receptors on cyclic AMP synthesis only occurs if the density of activated receptors is high enough to saturate the G(i) proteins and proportionate to the receptors' low affinity for the G(s) proteins. It tends to be abolished by receptor internalization.
Keywords: Receptors, Muscarinic; Cholinergic Agonists; lékové interakce; receptor muskarinový M2; Time Factors; Cyclic AMP; oxyfenon; CHO buňky; Dose-Response Relationship, Drug; cholinergní agonisté; Animals; agonisté muskarinových receptorů; cholerový toxin; časové faktory; Muscarinic Agonists; vztah mezi dávkou a účinkem léčiva; Drug Interactions; Humans; N-Methylscopolamine; Receptor, Muscarinic M2; N-methylskopolamin; AMP cyklický; tritium; Tritium; antagonisté muskarinových receptorů; Oxyphenonium; GTP-Binding Protein alpha Subunits, Gi-Go; křečci praví; vazebná místa; Cholera Toxin; GTP-Binding Protein alpha Subunits, Gs; Cricetinae; karbachol; CHO Cells; zvířata; receptory muskarinové; Binding Sites; transfekce; proteiny vázající GTP - alfa-podjednotky Gs; lidé; proteiny vázající GTP - alfa-podjednotky Gi-Go; Muscarinic Antagonists; Carbachol; Transfection